Patterns of Odonata Assemblages in Lotic and Lentic Systems in the Ankasa Conservation Area, Ghana - Seidu, Issah; Nsor, Collins Ayine; Danquah, Emmanuel; Tehoda, Paul; Oppong, Samuel K. (International Journal of Zoology, 2019)
Our study examined Odonata assemblages distribution pattern and the predictive factors that accounted for this in the lotic and lentic water systems within the Ankasa Conservation Area (Ghana). A total of 23 sites with sampling protocol of 2 researchers per hour per sampling site were used to survey Odonata species over two seasons in the three water bodies (streams, rivers, and ponds). Broken stick model, individual-based rarefaction, and Renyi diversity ordering were employed to quantify community assemblages. Ordination technique was also used to determine the Odonata-environmental relationship. A total of 1403 individuals, belonging to 47 species (22 Zygoptera and 25 Anisoptera) in six families, were recorded. Species richness (Hc = 3.414, p = 0.169) and diversity (Hc = 1.661, p = 0.44) generally did not differ among the three water systems. However, from individual sites, ponds appeared mostly diverse (α-scale = 0.04, Renyi index (r) = 5.86 to α = 3.5, r = 3.12), in spite of their lowest species abundance and richness. At the suborder level, ponds equally exhibited the highest Anisoptera species richness (9.90 ± SE 0.640) compared with Zygopterans (0.80± SE 0.291). Overall, Anisopterans (K= 16.51, p= 0.00026) and Zygopterans richness (K= 16.39, p= 0.00023) differed significantly among the three subsystems, while Odonata composition also differed significantly among the various water bodies (ANOSIM: global R= 0.94, p<0.001). Flow rate, water temperature, channel width, and turbidity were the key predictive factors that influence the structure of Odonata species assemblages. The results highlight the need to improve the functional status of the lentic and lotic systems, with the ultimate goal of conserving diverse Odonata fauna and other sympatric freshwater biodiversity.